Widespread mutagenesis and chromosomal instability shape somatic genomes in systemic sclerosis - Sriram Vijayraghavan; Thomas Blouin; James McCollum; Latarsha Porcher; François Virard; Jiri Zavadil; Carol Feghali-Bostwick; Natalie Saini (Nature Communications)
Abstract Systemic sclerosis is a connective tissue disorder characterized by excessive fibrosis that primarily affects women, and can present as a multisystem pathology. Roughly 4-22% of patients with systemic sclerosis develop cancer, which drastically worsens prognosis. However, the mechanisms underlying systemic sclerosis initiation, propagation, and cancer development are poorly understood. We hypothesize that the inflammation and immune response associated with systemic sclerosis can trigger DNA damage, leading to elevated somatic mutagenesis, a hallmark of pre-cancerous tissues. To test our hypothesis, we culture clonal lineages of fibroblasts from the lung tissues of controls and systemic sclerosis patients and compare their mutation burdens and spectra. We find an overall increase in all major mutation types in systemic sclerosis samples compared to control lung samples, from small-scale events such as single base substitutions and insertions/deletions, to chromosome-level changes, including copy-number changes and structural variants. In the genomes of patients with systemic sclerosis, we find evidence of somatic hypermutation or kategis (typically only seen in cancer genomes), we identify mutation signatures closely resembling the error-prone translesion polymerase Polη activity, and observe an activation-induced deaminase-like mutation signature, which overlaps with genomic regions displaying kataegis.